Enhancing motivation and learning outcomes in Pancasila education through Kahoot-based interactive learning in elementary school (Diniyah: Jurnal Pendidikan Dasar, 2026)
Interactive digital media are increasingly needed to make Pancasila Education more engaging, meaningful, and responsive to elementary students’ learning needs. This study examined the implementation of Kahoot as an interactive learning medium to improve students’ motivation and learning outcomes in Grade V of SD Negeri 2 Rimpak. A classroom action research design was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through classroom observations, a learning motivation questionnaire, and achievement tests. The findings showed that Kahoot implementation became more effective when revised from an individual speed-based quiz into a collaborative, feedback-oriented learning activity. Students’ motivation increased from 62.5% in the pre-action stage to 78.6% in Cycle I and 91.4% in Cycle II. Learning outcomes also improved, with classical mastery rising from 53.6% to 71.4% and 89.3%, while the class mean score increased from 61.4 to 82.5. These results indicate that Kahoot can support motivational engagement, formative feedback, and conceptual understanding in elementary Pancasila Education. Keywords: classroom action research; elementary school; Kahoot; learning motivation; learning outcomes; Pancasila Education